2018
DOI: 10.3390/catal8070276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Vinyl Chloride Monomer over Carbon-Supported Tris-(Triphenylphosphine) Ruthenium Dichloride Catalysts

Abstract: A series of catalysts, including Ru/AC, φ-P-Ru/AC, φ-P-Ru/AC-HCl, and φ-P-Ru/AC-HNO 3 , were prepared and evaluated for the hydrochlorination reaction of acetylene. The test results reveal that the φ-P-Ru/AC-HNO 3 catalyst shows superior catalytic performance with an initial acetylene conversion of 97.2% and a relative increment of 87.0% within 48 h in comparison with that of the traditional RuCl 3 catalyst. The substitution of inorganic RuCl 3 precursor by organic φ-P-Ru complex species in the catalysts resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
(51 reference statements)
2
2
0
Order By: Relevance
“…The extra peaks at 558.7 and 1430.2 cm −1 could be attributed to Co−P and P−C vibrations, respectively. 40 The FT-IR spectra show an intense band around ∼2356 cm −1 (Figure S2, SI), which could be assigned to the vibrations of double bonds between carbon and nitrogen resulting from conjugation in the polymeric framework, and this similar observation has been identified by Pieczynśka et al 41 The corresponding peak intensity is decreased for Co 3 O 4 @POP and Co x P@POP, which may be due to the interaction between POP support and Co 3 O 4 and Co x P, respectively, in accordance with the previous report by Li et al 42 In another way, this peak could also be attributed to the adsorbed atmospheric CO 2 (or an artifact), which is not under consideration in our present investigation. 43 Electron Microscopy Analysis.…”
Section: ■ Experimental Sectionsupporting
confidence: 90%
“…The extra peaks at 558.7 and 1430.2 cm −1 could be attributed to Co−P and P−C vibrations, respectively. 40 The FT-IR spectra show an intense band around ∼2356 cm −1 (Figure S2, SI), which could be assigned to the vibrations of double bonds between carbon and nitrogen resulting from conjugation in the polymeric framework, and this similar observation has been identified by Pieczynśka et al 41 The corresponding peak intensity is decreased for Co 3 O 4 @POP and Co x P@POP, which may be due to the interaction between POP support and Co 3 O 4 and Co x P, respectively, in accordance with the previous report by Li et al 42 In another way, this peak could also be attributed to the adsorbed atmospheric CO 2 (or an artifact), which is not under consideration in our present investigation. 43 Electron Microscopy Analysis.…”
Section: ■ Experimental Sectionsupporting
confidence: 90%
“…Finally, the Ru 3p photoelectron lines of Ru 3p 3/2 and Ru 3p 1/2 had values of 464.6 and 486.8 eV, respectively (Figure D). Compared with previous literature, these values align strongly with the presence of Ru 4+ ions and RuO 2 . This was unexpected as ruthenium was initially added in its Ru 3+ form as ruthenium nitrosyl nitrate, suggesting that it was oxidized in solution to its higher +4 oxidation state. Ruthenium is known to behave in a complex manner; therefore, it is not necessarily unexpected in the acidic medium .…”
Section: Surface Contamination Speciationsupporting
confidence: 81%
“…Such stable catalysis of Ru–NC@MIL in terms of the catalytic time (150 h) and deactivation rate (0.009%/h) was evidently superior in the present study to that of other recently reported Ru-based catalysts under the same reaction conditions ( T = 180 °C, and GHSV (C 2 H 2 ) = 180 h –1 ) (Figure d and Table S8). ,, …”
Section: Resultsmentioning
confidence: 99%